Synthesis, evaluation of the biological activity against Trypanosoma cruzi and Leishmania donovani. Preliminary in silico ADMET studies of 5-nitroimidazole derivatives - Miguel A. Rodríguez; Ali Mijoba; Nereida J. Parra-Giménez; Zuleyma Blanco; Katiuska Chávez; Alirica I. Suárez; Esteban Fernandez-Moreira; Hegira Ramírez; Jaime E. Charris (European Journal of Medicinal Chemistry Reports)
The synthesis and evaluation of the biological activity of a series of 5-nitroimidazole hybrids is described. The structures of the synthesized hybrids were confirmed by spectral analysis FT-IR, 1H NMR, 13C NMR, MS, and by Elemental Analysis. The toxicity (ADME/Tox) assessment study were carried out to predict the molecular properties associated with pharmacokinetic aspects of novel compounds. The trypanocidal and leishmanicidal activities of all synthesized hybrids were evaluated, compounds 7a and 8b were active against the epimastigote form of T. cruzi. Compound 10b showed marginal activity against the promastigote form of L. donovani. Sulfonyl derivative 8b was the most promising compound with IC50: 9.58 ± 2.02 μM and with a selectivity index (SI) greater than 31.31, that justifies the description as a promising hit for further study as a possible antichagasic agent.